AI-Based Digital Transformation Strategy: A Case Study of XYZ Hospital - Ananta, Rizki; Utari, Deasy Farah; Satria, Riri (Dinasti Research, 2026)
Teaching hospitals in developing countries face a critical challenge in adopting artificial intelligence (AI) due to the absence of structured roadmaps aligned with institutional strategy and business processes. This study presents an AI-based digital transformation roadmap for XYZ Hospital, a university-affiliated teaching hospital in Indonesia with a triple mission of clinical service, medical education, and health research. A qualitative case study approach was employed, with primary data collected through interviews with the hospital's Project Management Office and analysis of institutional documents including an IT assessment, a business process mapping workbook of 54 processes cross-referenced against STARKES 2024, JCI 8th Edition, and HIMSS EMRAM standards, and the hospital's Strategic Plan 2025-2029. An IS/IT Strategy framework was applied through three sequential analytical tables translating organizational strategy into information systems and technology requirements. The analysis revealed significant digital maturity gaps across infrastructure, data integration, governance, and talent dimensions. The resulting roadmap spans three phases: digital foundation (2025-2026), initial AI deployment covering clinical decision support systems for real-time diagnostic alerts and automated discharge summary generation (2026-2027), and advanced analytics with smart hospital features (2028-2029). This roadmap provides structured guidance for XYZ Hospital and serves as a replicable reference for other teaching hospitals pursuing AI adoption